ANALYSIS OF PRODUCT ATTRIBUTES AND BRAND IMAGE RELATIONSHIP TO CONSUMER BUYING INTEREST (STUDY AT UD. VOLKL INDONESIA) IN SURABAYA - Agus Baktiono; Budi Juliansyah (Jurnal Ekonomi, 2019)
UD Volkl Indonesia is a sports equipment selling company that has a good target market for Indonesia .UD. This VOLKL is on the HR road. Muhammad, Ruko Baverly SURABAYA. UD. Volkl was founded for consumer demand from all over Indonesia as well as to expand the volkl brand tennis racket market. UD. Volkl in its production activities is more oriented towards providing sports equipment, especially racquets for the Indonesian market. Where the volkl company produces racket to support tennis athletes in the world, during the decade the volkl company has experienced fluctuations in sales up and down. However, volkl in its way expanded well and became the best in the national market. Therefore UD.Volkl Indonesia must think hard to achieve the output of its marketing program, purchase actions, and create loyal customers. Based on the tennis racket brand circulating in Indonesia, there are many kinds of products. The research objective was to determine the analysis of the relationship between product attributes and brand image on consumer buying interest (study at UD. VOLKL in Hr. Muhammad). This type of research is quantitative. The population of this study were all athletes and registered consumers with a total sample size of 97 respondents who bought the Volkl brand tennis racket at UD. Volkl Indonesia at HR. Muhammad Surabaya. The sampling technique in this study was purposive sampling. The data collection technique in this study was carried out by distributing questionnaires. The data analysis technique used is the Pearson product moment correlation. The results of the conclusions obtained in this study show that the product attribute variable (X1) has a strong relationship with the consumer purchase interest variable (Y) and the brand image variable (X2) has a strong relationship with the consumer purchase interest variable (Y).